Equilibrium Asset Prices and No-Arbitrage with Portfolio Constraints - Detemple, Jerome; Murthy, Shashidhar (Review of Financial Studies, 1997)
We examine intertemporal asset pricing when short sales are constrained in proportion to the value of an investor’s portfolio. All assets’ prices exceed every investor’s marginal utility of consumption-based valuation of the associated dividends if every investor finds himself constrained in some asset in some state; we exhibit such an equilibrium. An asset’s price decomposes into three (investor-specific) components: the consumption value of its dividends, a speculative value premium, and a collateral value premium. The validity of the no-arbitrage pricing approach is shown to depend critically on the difference between real securities and their synthetic counterparts.